Efficiency and safety of the integrated use of medical gases thermal heliox, nitric oxide and molecular hydrogen in patients with exacerbation of chronic obstructive pulmonary disease complicated by hypoxemic, hypercapnic respiratory failure and secondary pulmonary arterial hypertension in the post-COVID period - Ludmila V. Shogenova (Терапевтический архив)
Aim. To study the efficacy and safety of the combined use of thermal heliox (t-He/O2), nitric oxide (NO) and molecular hydrogen (H2) in patients with exacerbation of chronic obstructive pulmonary disease (COPD) complicated by hypoxemic, hypercapnic respiratory failure (RF) and secondary pulmonary arterial hypertension (PAH) in the post-COVID period.